2023
DOI: 10.1021/jacs.3c03773
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Iron Porphyrin-Catalyzed C–H Hydroxylation of Ethylbenzene

Abstract: Quasi-classical molecular dynamics (MD) simulations were carried out to study the mechanism of iron porphyrin-catalyzed hydroxylation of ethylbenzene. The hydrogen atom abstraction from ethylbenzene by iron-oxo species is the rate-determining step, which generates the radical pair of iron-hydroxo species and the benzylic radical. In the subsequent radical rebound step, the iron-hydroxo species and benzylic radical recombine to form the hydroxylated product, which is barrierless on the doublet energy surface. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 77 publications
3
13
0
Order By: Relevance
“…As such, rebound should occur even in the gas phase trajectories. 17,18 Taken together, these findings confirm the dynamical nature of the rebound processes and are consistent with the observations of Srnec, 30 Soler, 48 and Sarkar 15 that post-HAT rebound is indeed a dynamically controlled nonsynchronous concerted process, and HAT transition state and the post-HAT reactivity are dynamically coupled. 17,30 The dynamic coupling between the HAT transition state and the rebound product pathway can be rationalized based on the concept of dynamic matching, originally proposed by Carpenter 21,22 and popularized by Houk, Singleton, Doubleday, Hase, Tantillo, and others.…”
Section: ■ Computational Detailssupporting
confidence: 87%
See 3 more Smart Citations
“…As such, rebound should occur even in the gas phase trajectories. 17,18 Taken together, these findings confirm the dynamical nature of the rebound processes and are consistent with the observations of Srnec, 30 Soler, 48 and Sarkar 15 that post-HAT rebound is indeed a dynamically controlled nonsynchronous concerted process, and HAT transition state and the post-HAT reactivity are dynamically coupled. 17,30 The dynamic coupling between the HAT transition state and the rebound product pathway can be rationalized based on the concept of dynamic matching, originally proposed by Carpenter 21,22 and popularized by Houk, Singleton, Doubleday, Hase, Tantillo, and others.…”
Section: ■ Computational Detailssupporting
confidence: 87%
“…Based on a static transition-state reactive mode kinetic energy distribution model for synthetic heme and nonheme Fe-oxo complexes, Srnec has suggested that the HAT-initiated rebound versus dissociation corresponds to a nonequilibrium ballistic process . More recently, our direct dynamics simulations, and later trajectories by Houk, have established that most of the rebound reactions are dynamically concerted with HAT transition-state motion, albeit with some nonsynchronous/lagging motion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Houk and co-workers carried out a detailed molecular dynamics (MD) simulation to better understand the hydrogen abstraction and radical rebound steps in iron porphyrin catalyzed C–H bond hydroxylation of ethylbenzene . On the doublet energy surface, 45% of reactive trajectories led directly to the hydroxylated product when quasi-classical MD was carried out in the gas phase, while 56% led directly to the alcohol with an implicit DCM solvent model.…”
Section: Fundamentals Of Radical Pairsmentioning
confidence: 99%